IMPLEMENTASI KEBIJAKAN PROGRAM E-RETRIBUSI PASAR SEBAGAI UPAYA PENINGKATAN PELAYANAN DI KABUPATEN SIDOARJO - Elvira Intan Pramesti (Madika: Jurnal Politik dan Governance, 2023)
Regional autonomy is the ability for each autonomous region to develop its area according to the condition and situation of its society. The same applies to Sidoarjo Regency, where in efforts to improve services, innovations related to daily market fee payments were established through the Sidoarjo Regent Regulation No. 44 of 2017 regarding the procedure for using E-Retribution, explaining how traditional market fee policies were changed from being conventional to digital to make it easier to advance services in the form of market fees. This research uses Mazmanian and Sebaztier's theory (1983) with a qualitative-descriptive method, The informants for this research were authorized officials, fee collectors, and E-Retribution traders. Since the implementation of E-Retribution, there have been different receptions among the market implementers. Therefore, the most effective method was discovered using a barcode system, which was then implemented in the Larangan market and Porong market under various reception conditions. Various efforts were made to achieve the most effective method so that the impact of the policy can be felt, especially for implementers